Plasticity in the feeding ecology of native Ponto‐Caspian gobies suggests establishment success in their nonnative range. Issue 3 (2nd April 2019) - Tarkan, Ali Serhan; Tepeköy, Erdi G.; Karakuş, Uğur; Top, Nildeniz; Vilizzi, Lorenzo
Abstract: The feeding ecology of the two gobiid species monkey goby Neogobius fluviatilis and western tubenose goby Proterorhinus semilunaris was studied in four natural lakes of the Marmara Region (NW Turkey), with special emphasis on seasonal and ontogenetic shifts in diet. Both species had similar food composition consisting of zooplankton and detritus. However, diet composition of both species significantly varied amongst lakes, and particularly so for P. semilunaris with seasonal and ontogenetic differences. Diet composition and seasonal/ontogenetic differences were overall similar to other populations of these gobiid species from both their native and nonnative ranges. The present findings suggest high plasticity in the diet of these two gobies, which can opportunistically utilize available food resources.